150 Years of psychiatry at Göttingen University: lectures given at the anniversary symposium - Wedekind, Dirk; Spitzer, Carsten; Wiltfang, Jens (V&R unipress, 2019)
This volume focuses on the special historical moments of the third oldest University Psychiatry in Germany, which has been existing in Göttingen since 1866. Ludwig Meyer, appointed to Göttingen in 1866, was the third professor ordinarius for Psychiatry in Germany and the first person to have a finished Hospital. The contributors in this volume show a great insight in the history of the University Psychiatry in Göttingen from its beginnings, to its enlargement and crisis during the Third Reich unto recent developments of the last decades.
Keywords: Konferenzschrift -- 2016 -- Göttingen; Geschichte; Psychiatrie; Universitätsmedizin Göttingen; Geschichte 1866-2016; Klinik für Psychiatrie und Psychotherapie der Universitätsmedizin Göttingen